THE MATERIALS ANALYSIS OF THE GATHERINGS ROLLING CURVES INVESTIGATION IN TRACK SECTIONS WITH A RADIUS OF LESS THAN 350M - Rybkin, V. V.; Tsyhanenko, V. V.; Gubar, O. V.; Khalipova, N. V. (Science and Transport Progress, 2008)
The results of analysis of the rolling stock derailment in curve track sections, which took place on Ukrainian railways, are presented. The distribution of derailments under influence factors such as: the curve radius, the rolling stock speed, the type of a rolling stock derailed, and the derailment causes has been investigated. Also the analysis of track condition in curve sections according to the data of track measuring cars has been carried out.